Snake robot: current state of the art and future trend - Khan, Md. Raisuddin; Ahamad, Syed Masrur; Watanabe, Mitsuru Lukman (2008)
This paper discusses the current state of the art of research and future trend of research activity towards achieving mechanisms and technology for useful implementation of efficient snake robots. Snake robot is meant to mimic motion of a natural snake, which does not possess any limb. Natural snakes can undergo wide range of motion and are able to move over rough terrains without the danger of entanglement. Slender structure of the snake body help a snake to go inside narrow holes. Thus a snake robot able to mimic these features of a natural snake will be of extreme use in handling search and rescue operations, minimal invasive surgery and inspection of pipeline defects in petochemical industries. Snake robots, though seem to be a promising solution to wheel less locomotion, and hyper redundant robot mechanism in locating difficult to reach location, could not receive scientists? interest due to the involvement of multiple disciplines that require integration under some common umbrella. Due to the evolution of Mechatronics as an Engineering discipline during the last two decades, promising solutions to snake robot design are gradually coming out.